Fate of enteric viruses and bacteriophages in sequencing batch reactor treating domestic wastewater : Luận văn ThS. Kỹ thuật hoá học, vật liệu, luyện kim và môi trường: 605203 - Nguyen, Hoang Phuong Thao (2019)
Research purposes and significance Viruses cause harm to humans because they are very small in size and therefore move in water and can cause disease with very low dose. A group of viral pathogens, from within the human body, excrete through the feces, and overdisperse the drainage pipes. Currently, researchers have identified several types of enteric viruses in the domestic effluent (Wong et al., 2012) mainly including enteroviruses (EVs), rotaviruses (RVs), adenoviruses (AdVs), noroviruses (NVs) hepatitis A virus (HAV) and astroviruses (AVs). The virus is responsible for some infectious diseases such as gastroenteritis, conjunctivitis, and respiratory disease, both developed and developing countries throughout the world. Therefore, studying the behavioral characteristics, existence or inactivated of the viruses in the water treatment stages of the plant is the most important. It is complicated and expensive to analyze all types of virus. At present, many previous studies have tried to identify suitable viral indicators of wastewater treatment efficiency. Several studies have proposed F- specific coliphages can be a good indicator monitoring the virus removal from wastewater (Tree et al., 2003; Duran et al., 2003), because there have similar morphological characteristics with many enteric viruses suggesting that they have the same single-stranded RNA, icosahedral shape, less than 50nm, and they are more persistent than bacteria. FSpecific coliphages are bacteriophages that infect Escherichia coli cells. These FRNA coliphages include MS-2 in group I, GA in group II, Qβ in group III and SP in group IV. GII and GIII F-RNA phage genotypes was found primarily from human feces, while GI and GIV F-RNA phage genotype are involved in animal waste (Vinjé et al., 2004). The use of F- specific coliphages as indicators of the presence and behavior of enteric viruses and animal enteric viruses has always been attractive because of the easy of detection and low cost associated with plaque assay and for similarity to enteric viruses in terms of transport and survival characteristics. Scope and objective This research studied the fate of enteric viruses and bacteriophages during the phase of sequencing batch reactor treatment plant. Sequencing batch reactor (SBR) is a fill and draws activated sludge system. In this system, each tank in the SBR system is filled during a discrete period of time and then operated as a batch reactor. It means, once the reactor is full, it behaves like a conventional activated sludge system, but without a continuous influent or effluent flow. The aeration and mixing are discontinued after the biological reactions are complete, the biomass settles, and the treated supernatant is removed. The reason why this study chooses SBR system because the hydraulic retention time is time-based so there is no short-circuiting. The influent and effluent can be pair so it is easy to observe the treatment efficiency using only a grab sample. In addition, almost no research data in sequencing batch reactor for viruses’ removal. So SBR system is the good target for an assessment of virus. This study has three main objectives: 1.To investigate the removal of enteric viruses and F-RNA phages in SBR system. 2.To evaluate the concentration of enteric viruses and F-RNA phages in activated sludge. 3.To find out the relationship between FRNA phage specific group I, II, III, IV and enteric viruses.